Underweight and lipodystrophy…a medical conundrum - WS, Wan Juani; M, Azura Dina; Sukor, Norlela; Mustafa, Norlaila; AW, Norasyikin; Omar, Ahmad Marzuki; R, Subashini; Loh, Huai Heng; Shahar, Mohammad Arif; O, Mohd Rahman; Kamaruddin, Nor Azmi (Malaysian Endocrine and Metabolic Society, 2014)
Introduction: Patient with lipodystrophy is usually underweight, with a body mass index (BMI) of under 18.5 or a weight 15% to 20% below that of normal for age and height. Lipoatrophy on the other hand is loss of fat, particularly on the cheek, face, shoulder and limbs. We herewith report a 51 year old lady with a clinical diagnosis of lipodystrophy. She has been underweight since her late 20’s. Her weight was 25 kg, height 155 cm and BMI 11kg/m2. She was otherwise healthy with no other systemic symptoms to suggest gastrointestinal, connective tissue, neurology or endocrine disorders. Clinical examination revealed a very thin and cachectic lady with generalised loss of fat, especially in the cheeks, temples, neck, shoulder, trunk, upper limbs and lower limbs. There was no acanthosis nigricans. She has no metabolic complications such as insulin resistance, cardiovascular disease, She has normochromic normocytic anaemia with a haemoglobin of 9.5 g/dl. Other investigations such as renal, liver, lipid, thyroid function test, albumin and creatinine kinase levels were normal. Connective tissue screening including C3, C4, rheumatoid factor and antinuclear antibody were negative. In 2004, she developed avascular necrosis of the left hip secondary to prolonged steroid use which was started in 1994 to improve her weight. She had osteoporosis with serial DEXA scan showing worsening of bone mineral density (BMD). Whole body DEXA scan was recently performed to assess her body fat distribution as she had refused any tissue biopsy. Her percentage of total body fat was 21.2% (25872g) which was adequate, hence excluded the diagnosis of lipodystrophy as a cause for being underweight. Her android/gynoid ratio was 0.79. Short of doing elaborate extensive investigations to diagnose lipodystrophy, we have resorted to the use of DEXA to confirm the presence of adipose tissue in this patient, thus excluding the diagnosis. As for her current treatment, she has been started on hormone replacement therapy to treat her osteoporosis.